2023
DOI: 10.1155/2023/5478666
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Total Amount of Enhanced Rainfall for a Cloud Seeding Experiment: Case Studies of Preventing Forest Fire, Drought, and Dust

Abstract: In this study, a method for verifying the effect of cloud seeding in the case of a mixture of natural and artificial rainfall bands was proposed, and its applicability to each experimental case was evaluated. Water resources that could be secured through cloud seeding were also quantified for the experiments on forest fire prevention, drought mitigation, and dust reduction in 2020. Data on numerical simulations, radar-derived rainfall, rain gauge-derived rainfall, and weather conditions were applied. Areas wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…While gaining visibility in the popular press, there is a scarcity of peer-reviewed research supporting or refuting the effectiveness of artificial rain for air pollution control. A recent study conducted in Korea stands out as the only one, and it reported slightly reduced PM 10 concentrations following two artificial rain events [9,10]. To address this gap and stimulate further research, this paper reviewed control theories behind this technology and indirect but relevant observations/findings, including air pollutant reduction after natural rain episodes and roadside sprinkling.…”
Section: Introductionmentioning
confidence: 99%
“…While gaining visibility in the popular press, there is a scarcity of peer-reviewed research supporting or refuting the effectiveness of artificial rain for air pollution control. A recent study conducted in Korea stands out as the only one, and it reported slightly reduced PM 10 concentrations following two artificial rain events [9,10]. To address this gap and stimulate further research, this paper reviewed control theories behind this technology and indirect but relevant observations/findings, including air pollutant reduction after natural rain episodes and roadside sprinkling.…”
Section: Introductionmentioning
confidence: 99%